Response surface optimization of syngas production from greenhouse gases via DRM over high performance NiâW catalyst - Yusuf, M. (Elsevier Ltd, 2021)
The process parameters for dry reforming of methane (DRM) over NiâW/Al2O3âMgO catalyst are optimized using response surface methodology (RSM). The NiâW bimetallic catalyst is synthesized by co-precipitation method followed by impregnation. The catalysts are characterized by BET, XRD, FESEM, EDX and TEM; to study physicochemical properties, morphology, composition, crystallite size and deposited carbon. The effect of process parameters, i.e., reaction temperature (600oCâ800 Â°C) and feed gas ratio (0.5â1.5) on the CH4, CO2 conversions and syngas ratio are studied. A temperature of 777.29 Â°C with CH4: CO2 of 1.11 at GHSV of 36,000 cm3gm.catâ1hâ1, delivered the CH4 and CO2 conversions of 87.6 and 93.3, respectively along with H2:CO of 1. The predicted process parameters were verified through actual experimental analysis at the optimized conditions, and results agreed with CCD of the RSM model with insignificant error. The MWCNT formed during DRM avoided catalyst deactivation and delivered stable performance over 12 h of reaction test at the optimized conditions. Â© 2021 Hydrogen Energy Publications LLC